Hypertension Management in Brazil: Usual Practice in Primary Care—A Meta-Analysis - Rafael V. Picon; Juvenal S. Dias-da-Costa; Flavio D. Fuchs; Maria Teresa A. Olinto; Niteesh K. Choudhry; Sandra C. Fuchs (International Journal of Hypertension)
Knowing the usual clinical practice is relevant for evaluations in health care and economic policies of management of hypertension. This study aimed to describe the usual management of hypertension in the Brazilian primary healthcare system through a systematic review and meta-analysis. The search of population-based studies conducted in Brazil was undertaken using PubMed, EMBASE, and Brazilian databases. Eligible studies were those conducted in adults with hypertension (blood pressure (BP) ≥ 140/90 mmHg or using BP lowering drugs). Three datasets’ data were analyzed: SESI study (in Brazilian workers); HIPERDIA (Brazilian Registration and Monitoring of Hypertensive and Diabetic Patients Program); and a population-based study. Meta-analysis has been performed using the fixed and random effect models. A total of 11 studies or data sets were included in the systematic review. Hypertensive individuals had, on average, 2.6 medical visits annually and 18.2% were on diuretics (n=811 hypertensive patients) and 16.2% on ACE inhibitors (n=1768 hypertensive patients). BP control rate ranged from 43.7 to 67.5%; 35.5% had measured total cholesterol and 36.5% determined fasting plasma glucose in the previous 12 months. Thiazide diuretics and ACE inhibitors were the most used BP lowering medications as single drugs, but the control rate of hypertension is insufficient.